A Comparative Study of Static and Dynamic Elastic Modulus Using the Stress Wave Velocity Method in Bamboo - Junaid, Annisa (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
The current grading process of bamboo still relies on visual or conventional observations. Bamboo is a non-prismatic material, so it is challenging to determine its strength accurately without laboratory testing. One crucial parameter for predicting bamboo strength is the modulus of elasticity (MoE). This study focused on 12 stems of Petung Bamboo (Dendrocalamus asper), 12 stems of Wulung Bamboo (Gigantochloa atroviolacea), and 12 stems of Apus Bamboo (Giganthochloa apus) randomly selected from a bamboo store. Before testing, bamboo stalks must be visually inspected to observe bamboo details and ensure there are no defects or damages. In calculating the volume of bamboo (V) have two methods, One, predicted volume, denoted as VP, involves calculating the volume by only measuring the cross-sectional area of the bamboo's tip and the cross-sectional area of the base, which is then multiplied by the bamboo's length (L). Two, detailed Volume, symbolized as VD, refers to the meticulous calculation of bamboo volume. Testing was conducted using the stress wave velocity method to obtain dynamic modulus of elasticity values (MOEd). Bamboo flexural testing (destructive) was performed to obtain static modulus of elasticity (MOEs) and bending strength (MOR) values for bamboo. Regression modelling of the relationship between MOEs and MOEd (using predicted volume) for bamboo, regardless of species, showed a relatively low coefficient of determination, i.e., 0.488. This implies that the longer the bamboo was tested, the lower the precision of its volume. Testing using detailed volume calculations for dynamic modulus of elasticity resulted in a relatively high coefficient of determination, precisely 0.8406.